PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DALAM MENINGKATKAN HASIL BELAJAR IPS PESERTA DIDIK KELAS VIII - C. Adrevi, Sujarwo, S. Yuliani (JURNAL PENDIDIKAN IPS, 2026)
This study aims to determine the effect of the Two Stay Two Stray (TSTS) cooperative learning model on Social Studies (IPS) learning outcomes of eighth-grade students. The study employed a quantitative approach with a quasi-experimental design (nonequivalent control group design). The sample consisted of two classes with 30 students each: Class VIII G as the experimental class implementing the TSTS model and Class VIII D as the control class implementing the Think Pair Share (TPS) model. The research instrument was a multiple-choice test with a reliability coefficient of 0.839. Data analysis included the Shapiro-Wilk normality test, Levene's Test of Homogeneity, and Independent Samples t-test for hypothesis testing. Results showed that the experimental class posttest mean of 89.29 was higher than the control class mean of 76.18. Hypothesis testing yielded a t-value of 5.417 with significance p < 0.001, indicating H₀ was rejected and H₁ was accepted. Effect size analysis using Cohen's d produced a value of 1.400, classified as a large effect. These findings prove that the Two Stay Two Stray cooperative learning model has a statistically significant effect and provides a strong practical impact on improving IPS learning outcomes of eighth-grade students.